Reforming of bioethanol in the system with reverse vortex air/Сo₂ flow of “Tornado” type with liquid electrode - Nedybaliuk, O.A.; Solomenko, Ol.V.; Chernyak, V.Ya.; Martysh, E.V.; Lisitchenko, T.E.; Simonchik, L.V.; Arkhipenko, V.I.; Kirillov, A.A.; Liptuga, A.I.; Belenok, N.V. (Вопросы атомной науки и техники, 2012)
In this paper we studied the reforming of bioethanol using the combined system that includes a plasma processing and handling in the pyrolysis chamber. As the plasma source was used plasma-liquid system with back-vortex flow of gas (a mixture of air and CO₂) and liquid electrode. Carbon dioxide was added in reforming the system to influence the plasma-chemical processes in the conversion of hydrocarbons. As the working fluid was used ethanol solution in distilled water (ratio C₂H₅OH/H₂O = 1/9,5). The system was investigated by emission spectroscopy, current-voltage characteristics, gas chromatography. Изучено реформирование биоэтанола с использованием комбинированной системы, которая включает плазменную обработку и обработку в пиролитической камере. В качестве источника плазмы была использована плазменно-жидкостная система с обратновихревым потоком газа (смесь воздуха и СО₂) и жидким электродом. Углекислый газ добавлялся в систему при реформировании для того, чтобы влиять на плазмохимические процессы конверсии углеводородов. В качестве рабочей жидкости использовался раствор этилового спирта в дистиллированной воде (соотношение C₂H₅OH/H₂O = 1/9, 5).Система была исследована с помощью эмиссионной спектроскопии, вольт-амперных характеристик, газовой хроматографии. Вивчено реформування біоетанолу з використанням комбінованої системи, яка включає плазмову обробку і обробку в піролітичній камері. В якості джерела плазми було використано плазмово-рідинну систему зі зворотновихровим потоком газу (суміш повітря і СО₂) з рідким електродом. Вуглекислий газ додавався в систему під час реформування для того, щоб впливати на плазмохімічні процеси конверсії вуглеводнів. В якості робочої рідини використовувався розчин етилового спирту в дистильованій воді (співвідношення C₂H₅OH/H₂O = 1/9, 5). Система була досліджена за допомогою емісійної спектроскопії, вольт-амперних характеристик, газової хроматографії.